Intergenerational partnerships in nursing: lessons from a plenary session at the 2019 International Council of Nurses' Singapore Conference. (20th August 2019) - Salmon, Marla E.; Walji, Sarah
Abstract: This year's International Council of Nurses' global Congress in Singapore featured a theme of strengthening collaboration and partnerships across generations. In their plenary session, the two authors of this article exemplified this theme in both the development and delivery of their session. Together, they developed a set of 'common ground' attributes of nursing policy leaders, reflecting the knowledge and experiences of two very different nursing policy leaders: one a 'Baby Boomer' nurse with almost five decades of national and global policy leadership, and the other, an early career 'Millennial' leader engaged in her first decade of global policy leadership work. Their collaboration resulted in a session featuring reflections on relevance across generations, using symbolic images and a 'Ted‐talk' style presentation, and active engagement of the audience. This article speaks to both the process for developing these 'common ground' attributes, and insights and lessons learned that can help inform future collaborations across generations of nurses.